The Long Walk: Considering the Enduring Spatial and Racial Dimensions of Deprivation Two Decades after the Fall of Apartheid - Ronelle Burger; Servaas van der Berg; Sarel van der Walt; Derek Yu (Institute for the Study of Labor (IZA), 2015)
This study examines the enduring spatial and racial dimensions of poverty and deprivation in South Africa to assess the progress made by the post-apartheid society and state. A multi-dimensional approach is required to assess progress because it can reflect the reduction in deprivation attributable to the improved affordability and expanded coverage of government services. While there has been previous studies tracking poverty trends over segments of the post-apartheid period, no previous work has considered multi-dimensional deprivation over the two decades following the official fall of apartheid. We adopt the Total Fuzzy and Relative approach proposed by Cheli and Lemmi (1995) to derive a poverty index with nine dimensions of deprivation, including education, employment, dwelling type, overcrowding, access to electricity, water, telephone, sanitation and refuse collection. Our analysis shows that there has been a significant improvement in South African deprivation levels between 1996 and 2011, but it also finds that geography and race continue to play an important role in explaining patterns of deprivation.
Keywords: I32; I38; N97; D31; 330; poverty; deprivation; fuzzy sets; South Africa